Women and work : exploring race, ethnicity, and class - Higginbotham, Elizabeth; Romero, Mary. (Thousand Oaks : SAGE, 1997)
This collection of original research articles explores how race, ethnicity, and social class have shaped the work lives of women. Women and Work explores women's working conditions, their wages and salaries, their abilities to control their work environments, and how they see themselves and their options in the workplace. A great deal of importance is given to women of color, non-citizens, and working-class women - groups that are often neglected in other treatments of this subject.
The integration of work and family, women's vision of their own work and consciousness as employees, and women's resistance to exploitative and limiting work are themes also addressed throughout this book. Written by an interdisciplinary group of women scholars, Women and Work will be of interest to faculty, researchers, and advanced students in the fields of sociology, organization studies, psychology, gender studies, women's history, and economics.
Includes bibliographical references and indexes.
Keywords: Women -- United States -- Economic conditions; Women -- United States -- Social conditions; Social classes -- United States; Ethnicity; United States -- Ethnic relations